Short Communication. Wood identification based on their common name and their transversal surface anatomy. Application to the batch from the expedition of Ruiz and Pavon - Villasante, A. (Forest Systems, 2013)
Aim of study: To identify species of wood samples based on common names and anatomical analyses of their transversal surfaces (without microscopic preparations). Area of study: Spain and South America. Material and Methods: The test was carried out on a batch of 15 lumber samples deposited in the Royal Botanical Garden in Madrid, from the expedition by Ruiz and Pavón (1777-1811). The first stage of the methodology is to search and to make a critical analysis of the databases which list common nomenclature along with scientific nomenclature. A geographic filter was then applied to the information resulting from the samples with a more restricted distribution. Finally an anatomical verification was carried out with a pocket microscope with a magnification of x40, equipped with a 50 micrometers resolution scale. Main results: The identification of the wood based exclusively on the common name is not useful due to the high number of alternative possibilities (14 for “naranjo”, 10 for “ébano”, etc.). The common name of one of the samples (“huachapelí mulato”) enabled the geographic origin of the samples to be accurately located to the shipyard area in Guayaquil (Ecuador). Given that Ruiz y Pavón did not travel to Ecuador, the specimens must have been obtained by Tafalla. It was possible to determine correctly 67% of the lumber samples from the batch. In 17% of the cases the methodology did not provide a reliable identification. Research highlights: It was possible to determine correctly 67% of the lumber samples from the batch and their geographic provenance. The identification of the wood based exclusively on the common name is not useful. Key words: historic wood; Ruiz and Pavon’s expedition; wood anatomy; wood identification; wood nomenclature.